The effects of vaginismus treatment and subsequent pregnancy: A case group study - Zahra Karimian; Marzieh Araban; Arezoo Haseli (Mashhad University of Medical Sciences, 2024)
Introduction: Considering the negative effects of vaginismus on the quality of life of couples and delay in pregnancy, this case group study was conducted with aim to investigate the process of treatment of patients with vaginismus and subsequent pregnancy. Cases presentation: In this descriptive study, 12 patients with vaginismus were evaluated from October 2021 to December 2023. After history and initial evaluation, vaginismus grades 3 and 4 were diagnosed based on the Lamotte scale in the examination of the patients. The participants aged 20-35 years old. The mean duration of this disease and the mean duration of infertility were 4.3 years and 4.1 years, respectively, and 5 patients (41.6%) wanted assisted reproductive methods. During this period, the patients had received several ineffective and unscientific treatments. The process of treatment was done as a team. The treatment was started by the reproductive and sexual health specialist, the trainings, follow-up of the patients and referral to the team members were also done by the same specialist. The process included cognitive behavioral therapy and dilators that during the treatment process, Kegel exercises and non-sexual sensation were also performed by the patient. The sessions were held weekly and treatment period lasted two to three months. After end of treatment, the patients were able to have sexual intercourse without pain and became pregnant 3 to 12 months after the treatment. Conclusion: One of the problems in women with vaginismus is infertility and this problem can be completely solved with scientific, team and combined treatments and persistence in the treatment process.